Feasibility study about using a stand-alone wind power driven heat pump for space heating. (15th October 2018) - Li, Hailong; Campana, Pietro Elia; Tan, Yuting; Yan, Jinyue
Highlights: This study studies a heat pump system directly coupled with a wind turbine for a detached house. The intermittency of wind energy results in significant thermal discomfort. Increasing the capacity of wind turbines does not necessarily lead to an improved thermal comfort. The battery system can effectively lower the loss of load probability. The time interval used in the dynamic simulation has significant influence on the results. Abstract: Reducing energy consumption and increasing the use of renewable energy in the building sector are crucial to the mitigation of climate change. Wind power driven heat pumps have been considered as a sustainable measure to supply heat to the detached houses, especially those that even do not have access to the electricity grid. This work is to investigate the dynamic performance of a heat pump system driven by wind turbine through dynamic simulations. In order to understand the influence on the thermal comfort, which is the primary purpose of space heating, the variation of indoor temperature has been simulated in details. Results show that the wind turbine is not able to provide the electricity required by the heat pump during the heating season due to the intermittent characteristic of wind power. To improve the system performance, the influences of the capacity of wind turbine, the size of battery and the setpoint of indoor temperature were assessed. It is found that increasing the capacity of wind turbines is not necessary to reduce the loss of load probability; while on the contrary, increasing the size of battery can always reduce the loss of load probability. The setpoint temperature clearly affects the loss of load probability. A higher setpoint temperature results in a higher loss of thermal comfort probability. In addition, it is also found that the time interval used in the dynamic simulation has significant influence on the result. In order to have more accurate results, it is of great importance to choose a high resolution time step to capture the dynamic behaviour of the heat supply and its effect on the indoor temperature.